(untitled) (Terr@ Plural, 2022)
The costs for carrying out representative and accurate measurements, in situ, for estimating laminar water erosion in large areas are quite expensive. The work aimed to spatialize and analyze the soil erosive susceptibility of the Dourados Watershed qualitatively way through the application of USLE/RUSLE and free geotechnologies. It can be observed that 46,2% of the Dourados river watershed presents a soil loss of fewer than 10 tons/ha.year. Regions with exposed soil, land use, and occupation with agricultural predominance along with soil factors with higher erodibility and specific topography (larger slopes) lead to large annual losses of soil (> 150 tons/ha.year) in 2,4% of the watershed.